Challenges facing the implementation of community and home-based early childhood development programmes for vulnerable children aged 0-4 years in the Western Cape and Eastern Cape, South Africa - Orgill, Marsha Sarah (Department of Political Studies, 2014)
This thesis examined the challenges facing the public sector implementation of community and home based early childhood development (ECD) programmes for vulnerable children aged 0-4 years in the Western Cape and Eastern Cape, South Africa. A qualitative case-study approach was used. The unit of analysis was the Department of Social Development (DoSD) as they are the public sector funders of non-profit organizations (NPOs) who deliver these services. The thesis included a literature review, a policy document review, and the collection and analysis of six interviews with officials involved in implementation of the National Integrated Plan for Early Childhood Development 2005–2010 (NIP for ECD). The data was organised using organizational coding and conceptually ordered displays, and analysed using the 5-C protocol of implementation as the overarching conceptual framework. The findings of the study showed that the main challenges facing the DoSD in the implementation of community and home-based ECD are: (1) Human resources that are stretched to capacity at the provincial and district level, primarily social workers who are unable to manage current services; (2) inadequate line item funding to scale up the provision of services in order to fulfill the mandate of the NIP for ECD (2005); (3) a shortage of NPOs to scale up services, current service providers already suffer with their own capacity constraints; (4) a lack of norms and standards for funding community and home-based ECD; (5) the social sector currently prioritizes centre-based ECD (in terms of funding and training) over community and home-based ECD. Another critical shortcoming is a lack of information regarding provision of services and a lack of South African evidence based research to assist implementers in making rationing decisions at the provincial level. Officials at the DoSD however display commitment to, and recognize the need to, support community and home-based ECD. The officials are however limited in doing so due to capacity constraints.